Mutations in FOXC2 in Humans (Lymphoedema Distichiasis Syndrome) Cause Lymphatic Dysfunction on Dependency - Mellor, Russell H.; Tate, Naomi; Stanton, Anthony W.B.; Hubert, Charlotte; Mäkinen, Taija; Smith, Alberto; Burnand, Kevin G.; Jeffery, Steve; Levick, J. Rodney; Mortimer, Peter S. (Journal of vascular research, 2011)
Background: Human lymphoedema distichiasis syndrome (LDS) results from germline mutations in transcription factor FOXC2. In a mouse model, lack of lymphatic and venous valves is observed plus abnormal smooth muscle cell recruitment to initial lymphatics. We investigated the mechanism of lymphoedema in humans with FOXC2 mutations, specifically the effect of gravitational forces on dermal lymphatic function. Methods: We performed (1) quantitative fluorescence microlymphangiography (FML) on the skin of the forearm (non-swollen region) at heart level, and the foot (swollen region) below heart level (dependent) and then at heart level, and (2) immunohistochemical staining of microlymphatics in forearm and foot skin biopsies, using antibodies to podoplanin, LYVE-1 and smooth muscle actin. Results: FML revealed a marked reduction in fluid uptake by initial lymphatics in the LDS foot during dependency, yet normal uptake (similar to controls) in the same foot at heart level and in LDS forearms. In control subjects, dependency did not impair initial lymphatic filling. Immunohistochemical microlymphatic density in forearm and foot did not differ between LDS and controls. Conclusions:FOXC2 mutations cause a functional failure of dermal initial lymphatics during gravitational stress (dependency), but not hypoplasia. The results reveal a pathophysiological mechanism contributing to swelling in LDS.